The load-velocity relationship in the jump squat exercise - Irineu Loturco; Michael McGuigan; Lucas A. Pereira; Fernando Pareja-Blanco (Termedia Publishing House, 2022)
The purpose of this study was to test the load-velocity relationship in the jump squat (JS) exercise using three different velocity parameters (mean velocity [MV], mean propulsive velocity [MPV], and peak velocity [PV]). Twenty-six male rugby union players (24.3 ± 3.9 years; 1.81 ± 0.09 m; 101.3 ± 15.4 kg) performed a progressive loading test in the JS with loads corresponding to 20, 40, 60, and 80% of the half-squat 1RM (equivalent to 24, 46, 70, and 94% of the estimated JS-1RM). MV, MPV, and PV were continuously recorded during all attempts using a linear velocity transducer. Linear regression models were used to determine the relationships between JS loads and MV, MPV, and PV. Bar-velocity outputs demonstrated high levels of consistency and reliability (coefficient of variation ≤ 5% and intraclass correlation coefficient ≥ 0.90). The predictive power of MV, MPV, and PV were ≥ 91%, for all tested variables (P < 0.0001). The equations and bar-velocity values provided in this study can be used by coaches to precisely determine and prescribe JS training loads, from verylight to heavy loading conditions (i.e., ~20-100% JS 1RM).